BASIC DUTIES AND FORMS OF ACCOUNTING OF LABOR AND WAGE (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2024)
In this article, we will consider what are wages, wages and their tasks, wage forms, definition set and definition rate. At the same time, we will study the differences between discharges, basic and additional wages.